Disseminated cryptococcosis in a child with liver transplantation: a case report - Barut, Doğan; Kunay, Bora; Yıldırım Arslan, Sema; Akkuş, Gözde Kayalı; Şahbudak Bal, Zümrüt; Yazıcı, Pınar; Karakoyun, Miray; Aydoğdu, Sema (The Turkish journal of pediatrics, 2024)
Background. Cryptococcus neoformans causes cryptococcosis, primarily affecting immunocompromised individuals, including solid-organ transplant recipients, and, less frequently, immunocompetent people. Case. A 15-year-old male with congenital hepatic fibrosis, portal hypertension, and cirrhosis underwent orthotopic liver transplantation. He received perioperative antimicrobial and antifungal prophylaxis and continued immunosuppressive treatment. Thirty months post-transplant, he presented with fever, hypertension, and sacroiliac joint pain. Peripheral blood cultures showed C. neoformans, confirmed by pan-fungal polymerase chain reaction assay and latex agglutination tests. Despite initial treatment with intravenous (IV) fluconazole, his condition worsened, necessitating intubation for acute hypoxic respiratory failure. Magnetic resonance imaging and computed tomography scans indicated disseminated cryptococcosis with lymphadenitis, possible meningitis, and pneumonia. Treatment was escalated to IV liposomal amphotericin B and 5-flucytosine, while reducing immunosuppressive treatment. Despite negative fungal cultures on the tenth day, the patient deteriorated, developing pancreatitis, pneumonia, and massive gastrointestinal bleeding, leading to death on the 35th day of hospitalization. Conclusion. This case shows the severity and complexity of managing disseminated cryptococcosis in pediatric liver transplant recipients. Aggressive therapy and early identification are essential for improving outcomes in these high-risk patients.